2017
DOI: 10.1155/2017/5429063
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Toxicity of Polylactic Acid/Ferrosoferric Oxide Nanomagnetic Microsphere

Abstract: Magnetic targeted drugs delivery system (MTDDS) is a new targeted drug system, which can greatly reduce the dosage and improve the therapeutic efficiency of medicine. Currently superparamagnetic ferric oxide plays important function as targeted drug in the treatment of tumors, but cytotoxicity was still regarded as side effect in the process of drug. In this paper, we take advantage of drug carrier (ferric oxide) toxicity controlling cancer cell growth in cancer treatment, increasing targeted drug efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Serum inorganic phosphate concentration showed a significant increase and decrease (P<0.05) in all groups during 8 weeks as a result of bone repairing process (46). Serum urea concentration showed a significant increase (P<0.05) 8 weeks post-implantation in group D which signified kidney disease (51,52). The changes in haematological and biochemical parameters recorded from this study were related to the cascade of immunological responses caused by materials that used in the development and coating the scaffolds.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Serum inorganic phosphate concentration showed a significant increase and decrease (P<0.05) in all groups during 8 weeks as a result of bone repairing process (46). Serum urea concentration showed a significant increase (P<0.05) 8 weeks post-implantation in group D which signified kidney disease (51,52). The changes in haematological and biochemical parameters recorded from this study were related to the cascade of immunological responses caused by materials that used in the development and coating the scaffolds.…”
Section: Discussionmentioning
confidence: 59%
“…According to the liver, spleen and kidney histological properties, an abnormal architecture was observed in all animals thus indicating the form of toxicity related to the products released from the degrading scaffold materials. The severity of the histopathological lesions in the viscera were coated polymers dependent nor development materials and in agreement with earlier reports by Harlan Laboratories (54) and Aguilar et al (55) that documented the absence of treatment-related effects from studies on oral administration of calcium carbonate, Isa et al (56) who has demonstrated the biocompatibilities (nontoxicity and nonimmunogenicity) of CaCO3 nanocrystals and making it suitable candidate for nanomedicine and related fields, Hammadi et al (57) who proved that CaCO3 nanocrystals to be biocompatible and non-toxic by itself, Jaji et al (58) who repoted that CaCO3 is generally safe and the safety of CaCO3 nanocrystals in vivo is dependent on its concentration and route of administration, Zuki et al (15) and Bharatham et al (16) documented the absence of scaffolds materials effects to leak out as they degrade from studies in scaffolds of calcium carbonate, gelatin, dextrin, dextran and alginate, Lee et al (28), Gendler et al (59) and Wiebe et al (60) who reported possibly toxic repercussions of GTA for cells in the direct area; Athanasiou et al (51), Xiang et al (52) who reported toxicity effect and certain problems, especially pertaining to reduction in cell proliferation. The cytocompatibility of the scaffold materials towards cells has been previously proven through in vitro evaluations and it is unlikely for the scaffold materials to cause an adverse toxicity reaction at distant organs of the animals in in vivo evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Pocos estudios sobre el uso de nanopartículas de hierro con PLA en prótesis ha sido estudiada, su objetivo se basa en generar memoria reprogramable inducida magnéticamente en un derivado de PLA, con ácido poli-D,L-láctico (PDLLA), pudiendo aplicarse a prótesis no deformables (X. Zheng et al, 2009), o como agentes transportadores de fármacos usando PLA (Xiang et al, 2017). En la inves-tigación de Zhou et al (2013) se fabricaron y caracterizaron andamios de cristales de nanocelulosa (CNC) y anhídrido maleico (MAH) injertados en PLA, como matriz (MPLA/ CNC).…”
Section: Nanopartículas De óXido De Hierrounclassified
“…Both fundamental physical discoveries and new biological and medical applications are likely to continue to emerge using these techniques. Recent in vitro and in vivo studies confirmed the biocompatibility of the microspheres and the extracts of the microspheres showed no cytotoxic reactivity in the cytotoxicity tests [15], [16]. Experiments also showed that polylactic acid (PLA) coated microspheres containing superparamagnetic Fe 3 O 4 nanoparticles, injected in mice, had no effect on their main organs and blood biochemistry, its performance conforms to clinical requirements, and its biocompatibility conforms to the standard for medical material [16].…”
Section: Introductionmentioning
confidence: 99%